Social development and absolute poverty in Asia and Latin America - De Geyndt, Willy, 1932- 1932- (World Bank technical paper, 1996)
"Using econometric techniques analyzes causes of widespread poverty in Latin America and the 10 largest East and South Asian countries. Concludes that slow economic growth is not the only explanatory variable, and cites importance of schools and health care"--Handbook of Latin American Studies, v. 57